Understanding Christians' underrepresentation in STEM and why it matters - Rios, Kimberly; Mackey, Cameron D.; Cheng, Zhen Hadassah (Frontiers in Social Psychology, 2023)
In many Western societies, religious people (particularly Christians) are underrepresented in STEM fields, relative to their numbers in the general population. We review existing literature that supports two broad types of explanations for religious underrepresentation in STEM, focusing primarily on Christians in the US. First, Christianity and science may actually conflict or be perceived by Christians to conflict with one another, which reduces Christians' engagement in STEM fields. Second, science and scientists may be portrayed, and Christians stereotyped, in ways that lead Christians to believe they would not belong in STEM. We argue that it is critical to further investigate these explanations, as doing so will shed light on how to broaden participation and engagement in science among a sizeable chunk of the population. We conclude our review by discussing promising directions for future research and implications for non-Christian religions, as well as in contexts outside the West.